Removal of ammonium and nitrate by water lettuce (Pistia Stratiotes) under salinity stress - Toan Nguyen-Sy; Huynh Hai; Hong Hanh Do; Phu Tran Thi; Thao Tran Minh; Ngoc-Son Tran; Cuong Doan Chi; Minh Vo Van (Egyptian Journal of Aquatic Research)
The present study investigated plant biomass and nitrogen (form of ammonium and nitrate) removal by water lettuce (Pistia Stratiotes) under different salinity stress levels. Four treatments were set up as follows: control (500 mL distilled water + 10 mg N L−1), control + 0.1 % NaCl, control + 0.25 % NaCl, and control + 0.5 % NaCl. After 17 days, solutions were collected to measure nitrogen removal and plant biomass, while pH and salt concentration were measured every three days. The ammonium and nitrate removal ranged from 42.6 % to 63.5 % and from 33.7 % to 62.5 %, respectively, at the end of the process and had a negative correlation with salt concentration; however, there was no significant difference observed with low salinity levels (<0.25 % NaCl). Interestingly, water lettuce loaded the same amount of nitrogen removal in both environments under non-salinity stress; in the NaCl-contaminated environment, plant-loaded ammonium removal was better than that in the nitrate environment. Water lettuce survives well at up to 0.5 % NaCl in ammonium environments; however, it dies in nitrate environments. Additionally, 0.25 % NaCl likely promoted plant growths in an ammonium environment but not in a nitrate environment. In conclusion, water lettuce is a potential phytoremediation agent under low salt stress conditions.